(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
Population fertility and its related patterns of reproductive behavior constitute one of the main axes of demographic research concerns. There have been several attempts to frame fertility theoretically as being a complex phenomenon, in which overlap very intricate economic, social, cultural, biological and subjective factors. Among all factors affecting fertility, this paper is interested in the psychological subjective dimension that affects human reproduction in itself, and in its complex interactions with societal conditions and constraints. It proceeds from an interdisciplinary perspective and examines how demography uses psychological knowledge in adjusting concepts related to the reproductive behavior of the population, and seeks to highlight the value of the child in its psychological and social connotations. It also raises the reproductive question in the light of gender issues and roles entrusted to men and women, and their changes. Moreover, it discusses reproductive desires and intentions, the conceptual problems related to their use, and their repercussions in the results of the habitual quantitative surveys in fertility studies. This study is, therefore, an attempt to get away from the stereotypical knowledge of population fertility, towards a level that relates more closely to the reality of human being as an individual on one hand, and as an individual within a social system on the second hand. It highlights the cognitive addition that maybe provided by the engagement of demographic research in an interdisciplinary work, a work that benefits from the broad helpful cognitive system that can be offered by other social and human disciplines. At the same time, the study is concerned with raising the methodological standards that we need to adopt in this kind of interdisciplinary thinking, in order to reach through it to a more disciplined knowledge of this complex phenomenon.